THE EFFECTS OF SOCIAL MEDIA ON COMMUNICATION PROFICIENCY OF ENGLISH LANGUAGE LEARNERS (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
The proliferation of social media has profoundly reshaped linguistic practices, especially among its active users. This study investigates the multifaceted influence of these platforms, analyzing not only their role in facilitating widespread dissemination of ideas and experiences but also their contribution to the genesis of novel linguistic forms characteristic of the digital age. The research will delve into the complex interplay between established communication norms and the emergent vernaculars of online interaction, exploring the implications for both individual communication styles and the broader evolution of language itself. This includes an examination of how social media's unique affordances such as brevity, visual integration, and asynchronous communication shape the development and adoption of these new linguistic features.